Japanese Semi-Military Organizations in Indonesia: From Formation to the End of the Organizational Period - Nabila, Putri; Harnum, Sintia; Tanjung, Muhammad Fahrizal (Holistic Science, 2024)
This article discusses the semi-military organization formed by the Japanese government, how this semi-military organization has contributed to Indonesia. Written using the literature method, which is carried out to overcome the findings of the discussion by reading scientific journals, books or articles related to this field. Thus the semi-military organization has little or a lot of impact on preparing for Indonesian independence. At first this organization emerged as a response to the political or social at that time which was often organized to protect the community from internal and external threats, until finally it became increasingly involved in the struggle for independence in its role to train and arm freedom fighters.